Análise de casca de alvenaria cerâmica armada: tipo parabolóide hiperbólico - Roberto Fontes (2005)
In the present publication, the design and construction of a roof for a church, shaped as a hyperbolic parabolóid and made with reinforced brick masonry is presented. The roof was built in 1987 in Belo Horizonte, Brazil. The brick used was the common one glazed, used in unplastered exterior masonry. A comparison is made between the original design, using membrane theory and elastic linear analysis with finite element computer program and results are presented. Also a non- linear analysis is made. The analysis with membrane theory was performed in FORTRAN, with a computer program, updated, published in the JOURNAL OF THE AMERICAN CONCRETE INSTITUTE in January 1970. The elastic linear and non-linear analysis where performed with the DIANA.8 computer program. The membrane theory compared with elastic linear analysis gave compatible results, and detain the essential for a safe design, as expected for the structure analyzed, with span no longer than 30 m and as the fact that the roof was not too flat. Nowadays the structure is in good state of conservation, and since its construction, the waterproof was only once remade. The membrane theory, heavily used before the desk computer era, was applied successfully in several shells structures since then.